2011
DOI: 10.4103/0974-777x.91051
|View full text |Cite
|
Sign up to set email alerts
|

Improving diagnosis of Trichomonas Vaginalis infection in resource limited health care settings in Sri Lanka

Abstract: Objective:This study was designed to compare diagnosis of trichomoniasis by culture, wet smear examination, and Giemsa stain. A modified technique was used to transport and prepare the specimen to ensure parasite viability prior to Giemsa staining.Materials and Methods:A clinic-based prospective study was carried out in association with the National STD/AIDS Control Programme over a period of 18 months. Three swabs were collected from the posterior fornix of 346 newly registered female patients for diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
6
1
Order By: Relevance
“…In this study risk factors like vaginal discharge, vaginal itching, dysuria, dyspareunia, and contraceptives used before pregnancy had significant association with T. vaginalis infection which is consistent with other studies conducted in Iran [13], Sri Lanka [16,17], and India [14].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study risk factors like vaginal discharge, vaginal itching, dysuria, dyspareunia, and contraceptives used before pregnancy had significant association with T. vaginalis infection which is consistent with other studies conducted in Iran [13], Sri Lanka [16,17], and India [14].…”
Section: Discussionsupporting
confidence: 81%
“…The finding of this study was lower than reports from Nigeria 18.66% [12], Tehran 10.2% [13], India 8.5% [14], Zambia 27.1% [15], Sri Lanka 6.9% and 7.2% [16,17], Maharashtra India 12.06% [18], Sudan 7.3% [19], and Maryland 12.6% [20].…”
Section: Discussioncontrasting
confidence: 55%
“…In one study it was reported that giemsa staining had high sensitivity (100%) and specificity (99.69%) compared to culture. The high sensitivity (100%) reported in their study was attributed to centrifugation of sample prior to preparation of smears which led to concentration of large number of parasites [21]. In set up lacking immediate microscopic facilities giemsa staining is very useful, where prepared and fixed smears can be transported to the laboratory for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the sensitivity of wet mount examination ranges between 35-80% depending on the technical expertise of the observer [8]. In one of the study it was shown that the sensitivity and specificity of direct wet mount microscopy was 95.83% and 100% respectively, in comparison to culture [21]. Although, positive wet mount is diagnostic, a negative test cannot exclude trichomoniasis because of low sensitivity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Self-medication should be avoided among women, they should seek the help of health care givers where necessary. Through this (Fernando et al, 2011) laboratory investigations are done to detect this organism and appropriate drugs would be administered. Good cleaning and disinfecting habits are advised, especially in the use of toilet and wears, example towels.…”
Section: Discussionmentioning
confidence: 99%